1999
DOI: 10.1074/jbc.274.13.8421
|View full text |Cite
|
Sign up to set email alerts
|

Mutants in ABC10β, a Conserved Subunit Shared by All Three Yeast RNA Polymerases, Specifically Affect RNA Polymerase I Assembly

Abstract: ABC10␤, a small polypeptide common to the three yeast RNA polymerases, has close homology to the N subunit of the archaeal enzyme and is remotely related to the smallest subunit of vaccinial RNA polymerase. The eucaryotic, archaeal, and viral polypeptides share an invariant motif CX 2 C. . . CC that is strictly essential for yeast growth, as shown by site-directed mutagenesis, whereas the rest of the ABC10␤ sequence is fairly tolerant to amino acid replacements. ABC10␤ has Zn 2؉ binding properties in vitro, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Rpb10 has a strong conservation along eukaryotic sequences with 41 identical amino acid positions in fungal, plant and human sequences [73]. In addition, Rpb10 shows a close homology to the N subunit of archaeal enzyme [12,54,74] and is loosely related to the smallest enzyme of cytoplasmic DNA viruses [73,75,76].…”
Section: Rpb10mentioning
confidence: 99%
See 4 more Smart Citations
“…Rpb10 has a strong conservation along eukaryotic sequences with 41 identical amino acid positions in fungal, plant and human sequences [73]. In addition, Rpb10 shows a close homology to the N subunit of archaeal enzyme [12,54,74] and is loosely related to the smallest enzyme of cytoplasmic DNA viruses [73,75,76].…”
Section: Rpb10mentioning
confidence: 99%
“…In vivo studies in budding yeast have demonstrated that Rpb10 can be functionally replaced by its human homologue (RPB10) [12]. Nevertheless, the N subunit of archaeal cannot replace Rpb10 in vivo [73]. However, yeast/archaeal chimeras are largely interchangeable, pointing to a conserved function in their respective transcription complexes [12].…”
Section: Rpb10mentioning
confidence: 99%
See 3 more Smart Citations